Corporate Environmental Responsibility and Female Directors as Drivers of Firm Profitability - Sri Maryati; Trie Sartika Pratiwi; Lisa Mandasari (Academia Open, 2025)
General background: The growing global concern for gender equality and environmental sustainability has encouraged companies to integrate inclusivity and ecological responsibility into their governance systems. Specific background: In Indonesia, the roles of female directors and corporate environmental responsibility engagement (CERE) are increasingly recognized as essential to strengthening corporate performance, yet their simultaneous influence remains insufficiently studied. Knowledge gap: Previous research has produced inconsistent results on how managerial ownership, gender diversity, and environmental engagement affect profitability, particularly in manufacturing firms. Aims: This study investigates the effects of CERE, managerial ownership structure, and the presence of female directors on firm performance among manufacturing companies listed on the Indonesia Stock Exchange for the period 2021–2023. Results: Using a quantitative method with Warp PLS and 243 firm-year observations, the findings indicate that both CERE and the presence of female directors significantly improve profitability, whereas managerial ownership structure shows no significant effect. Novelty: The study offers new insight by demonstrating that environmental responsibility and gender diversity jointly enhance performance regardless of ownership concentration. Implications: The results highlight the strategic importance of empowering women in leadership and implementing sustainable environmental practices to improve corporate outcomes in emerging markets. Highlights: Female directors and CERE significantly enhance firm profitability. Managerial ownership structure shows no significant effect on performance. Integrating gender diversity and environmental responsibility strengthens sustainable corporate growth. Keywords: Environmental Responsibility, Female Directors, Ownership, Profitability, Sustainability